It is known that 3 cos 7 2 π + 3 cos 7 4 π + 3 cos 7 8 π = 3 a 1 ( b − c 3 d ) , where a , b , c , d are positive integers, with g cd ( a , b ) = 1 and d cube-free.
Find a + b + c + d .
Note: Use the convention that 3 x = − 3 − x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
To solve this problem, we need to construct a cubic equation with the roots cos 7 2 π , cos 7 4 π , cos 7 8 π . Then we find the sum of the cube roots of that equation.
Starting from the 7 t h roots of unity, the roots of x 7 − 1 = 0 are { e 7 1 2 n π i ∣ n = 0 , 1 , … , 6 }
By factoring x 7 − 1 = ( x − 1 ) ( x 6 + x 5 + x 4 + x 3 + x 2 + x + 1 )
We know that the roots of x 6 + x 5 + x 4 + x 3 + x 2 + x + 1 = 0 are { e 7 1 2 n π i ∣ n = 1 , … , 6 }
Deviding both sides by x 3 , we have ( x 3 + x 3 1 ) + ( x 2 + x 2 1 ) + ( x + x 1 ) = 0
By the substitution u = x + x 1 , u 2 − 2 = x 2 + x 2 1 and u 3 − 3 u = x 3 + x 3 1 ,
the equation reduces to u 3 + u 2 − 2 u − 1 = 0 , and the roots
{ e 7 1 2 n π i + e − 7 1 2 n π i ∣ n = 1 , … , 6 } = { 2 cos 7 2 n π ∣ n = 1 , 2 , 3 } = { 2 cos 7 2 π , 2 cos 7 4 π , 2 cos 7 8 π }
Note that ⎩ ⎨ ⎧ cos 7 6 π = cos 7 8 π cos 7 4 π = cos 7 1 0 π cos 7 2 π = cos 7 1 2 π , and the Euler's identity e i θ = cos θ + i sin θ
The next step is to find the sum of the cube roots of u 3 + u 2 − 2 u − 1 = 0
Let the roots of u 3 + u 2 − 2 u − 1 = 0 be a 3 , b 3 , and c 3 .
By Vieta's formulae, a 3 + b 3 + c 3 = − 1 , and a 3 b 3 + b 3 c 3 + a 3 c 3 = − 2 , and a 3 b 3 c 3 = 1
Substituding them in
a 3 + b 3 + c 3 − 3 a b c = ( a + b + c ) 3 − 3 ( a + b + c ) ( a b + b c + a c )
a 3 b 3 + b 3 c 3 + a 3 c 3 − 3 a 2 b 2 c 2 = ( a b + b c + a c ) 3 − 3 a b c ( a + b + c ) ( a b + b c + a c )
and letting p = a + b + c and q = a b + b c + a c
we obtain the equations { p 3 = 3 p q − 4 q 3 = 3 p q − 5
Multiplying them we get ( p q ) 3 − 9 ( p q ) 2 + 2 7 p q − 2 0 = 0 , which, by completing the cubes, reduces to ( p q − 3 ) 3 + 7 = 0
So p q = 3 − 3 7 , hence p = 3 5 − 3 3 7 and q = 3 4 − 3 3 7
Finally we have 3 cos 7 2 π + 3 cos 7 4 π + 3 cos 7 8 π = 3 2 p = 3 2 1 ( 5 − 3 3 7 )